2013
DOI: 10.4236/jct.2013.41a006
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Survival Analysis on Runx3 Gene Expression in the Primary Tumor of Patients Suffering from Stomach Carcinoma

Abstract: Background: Runt domain transcription factor 3 (Runx3) is a putative tumor suppressor in human neoplasia. Previous researches suggested that a lack of Runx3 function contributed to human gastric carcinogenesis, however, it is not clear whether Runx3 is closely associated with clinicopathological features of primary stomach tumor and survival rate of patients. Aims: The article is to investigate the influence of survival analysis on Runx3 gene expression in the primary stomach tumor. Methods: Runx3 mRNA express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
1
0
0
Order By: Relevance
“…3). These results support our previous studies (23), which revealed that the low expression of Runx3 in primary gastric cancer was associated with a significantly shorter survival.…”
Section: Discussionsupporting
confidence: 93%
“…3). These results support our previous studies (23), which revealed that the low expression of Runx3 in primary gastric cancer was associated with a significantly shorter survival.…”
Section: Discussionsupporting
confidence: 93%